Mitigating Climate Change : Growth-Friendly Policies to Achieve Net Zero Emissions by 2050 - Jaumotte, Florence (IMF Working Papers; Working Paper ;, 2021)
Background paper prepared for the October 2020 IMF World Economic Outlook. This paper provides a detailed presentation of the simulation results from the October 2020 IMF World Economic Outlook chapter 3 and an additional scenario with carbon pricing only for comparison with the comprehensive policy package where green investments were also included. This paper has greatly benefitted from continuous discussions with Oya Celasun and Benjamin Carton on the design of simulations; contributions from Philip Barrett for part of the simulations; and research support from Jaden Kim. We also received helpful comments from other IMF staff. All remaining errors are ours. McKibbin and Liu acknowledge financial support from the Australian Research Council Centre of Excellence in Population Ageing Research (CE170100005).